POPULATION, FAMILIES, AND RACIAL INEQUALITIES IN MEXICO - Gomes, Cristina; Franco, Karla Denisse (Seven Editora, 2025)
This article analyzes demographic and socioeconomic aspects that differ between these excluded populations - indigenous and Afro-descendants, in contrast to the rest of the population. Mexico is a multi-ethnic country with a diverse population composed of European descendants, Afro-descendants, and Indigenous groups, the result of thirty thousand years of an evolving nation until the colonial invasion (1519 to 1521), followed by the colonial period (1521 to 1821), the trafficking and slavery of one hundred and fifty thousand African people, the independence wars (1810 to 1821), a Revolution (1910 to 1920) and the consolidation of the constitutional state, which includes eugenics by the Western assimilation of original peoples and African-descendants through education. This study compares three population groups according to their specific demographic variations in civil status, age at marriage, number of children, family structure, and level of education. The objective is to understand how these racialized groups differ in family behavior and the intersections between demographic and household characteristics. The quantitative methodology includes demographic methods to describe the patterns and differences between ethnically racialized groups and to explain how population reproduce racism conforming to structural and family inequalities. The results show that the demographic transition is less accelerated among indigenous and Afro-descendants, related to their lower level of education and other socio-economic vulnerabilities, but also to fertility and family structure and composition, leading to the need for support for the racialized women and elderly in the next decades, and multi-generational families. Conclusions show the need for specific affirmative policies oriented to support families of Indigenous and Afro-descendants.DOI: https://doi.org/10.56238/sevened2025.036-162